Harapan Orang Tua di Kampung Topeng Terhadap Pendidikan Anaknya - Nurfaizah, Rosania; Purnawati, Baiq Ayu Nisrina (Maliki Interdisciplinary Journal, 2025)
This study aims to understand parents’ expectations of children’s education in Kampung Topeng, Malang. A descriptive qualitative approach using semi-structured interviews was conducted with a mother with three children in Kampung Topeng. The results showed that mothers have high expectations for their children’s education, so that they can succeed and succeed in the future, including in terms of education. Mrs. PN, a research respondent, has high expectations for her children’s education for various reasons. First, because of her own experience of not being able to complete her education due to economic limitations. Second, because she wants to help the family economy. Third, because she wants her children to be successful and accomplished in the future. Mrs. PN has pathway thinking in achieving her goals in her children’s education, namely doing whatever it takes and working as hard as possible to fulfill her children’s educational needs. Mrs. PN has been busking for almost years, so she has an agency aspect, which is an individual’s ability to consider himself capable of achieving his goals in the way he chooses. Her expectations are not only to achieve academic performance, but also to build strong character and the ability to handle future difficulties. According to the thematic analysis, parental encouragement and effort are crucial in achieving children’s education. The results of this study can provide useful information for parents, teachers and everyone in an effort to improve the quality of education in Indonesia.